Penerapan Media Bergambar Terhadap Hasil Belajar IPAS Kelas VI MI Muhammadiyah Leksono - Deni Pangestu; Sri Jumini; M. Yusuf Amin Nugroho (STAI AL-AMIN, 2026)
This study aims to: 1) Investigate the application of visual media in improving the learning outcomes of IPAS for sixth grade students at MI Muhammadiyah Leksono. 2) To determine the difference in learning outcomes in IPAS between sixth grade students at MI Muhammadiyah Leksono who use visual media and those who do not. 3) To determine the improvement in learning outcomes in IPAS among sixth grade students at MI Muhammadiyah Leksono after the application of visual media. This study uses a quantitative research approach, specifically an experimental study. Data collection techniques include pretest and posttest methods, observation, questionnaires, documentation, and interviews. Data sources are obtained from primary and secondary data (references related to vectors, previous studies, articles, journals, and websites). The results of the study show that: 1) the teaching and learning process has often used conventional models, so that during teaching and learning activities, students often feel bored and tired. Pictorial media is not a new medium, but it has rarely been used for sixth grade students at MI Muhammadiyah Leksono. By using this medium, learning will become more interesting and students will be more enthusiastic in carrying out their learning. 2) IPAS learning of continental material using pictorial media for sixth grade students at MI Muhammadiyah Leksono can improve student learning outcomes, as evidenced by the gain test data showing that the N-gain score in the experimental class was 0.87955 with a very good criterion and an interpretation percentage of 87.95, which means it was effective. 3) There is a difference in learning outcomes between the experimental class and the control class. This is evidenced by the higher average posttest score of 93.8 for the class using visual media compared to 83.9 for the control class. This is in accordance with the t-test results, which show that tcount > ttable or 2.3 > 2.021 with a significance level of 5%. Therefore, Ha is accepted and H0 is rejected.